Bloody Burdens: Post-secondary Students and Menstruation on Campus - Smith, Lisa; Gacimi, Rim (Atlantis)

(untitled) (Mount Saint Vincent University, 2022)
In this paper, we discuss a qualitative data set that was gathered as part of a survey aiming to document access to menstrual supplies on campus and impacts on students. This research emerged in response to the growing interest in menstrual equity on campus, as well as literature examining student experiences of menstruation in the Global North. Through a thematic analysis, three main themes emerged: menstruation happens on campus, menstruation is managed on campus, and finally, the “solution” to the “problem.” Woven throughout the paper are notes on changes on the campus where the study took place and as the research unfolded—including the installation of barrier-free dispensers. In closing, we offer a postscript on the challenge of simple fixes—such as swapping out dispensers—in relation to addressing supports needed for menstruators. We found that menstruation is a burden that is experienced differentially by students, and outcomes and impacts cannot easily be confined to expected campus spaces, such as toilets. To this end, there is no easy fix, and we should not lose sight of the deeper and ongoing work ahead within post-secondary settings and beyond.